2004
DOI: 10.1080/10715760400017376
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Cell Growth by Overexpression of Manganese Superoxide Dismutase (MnSOD) in Human Pancreatic Carcinoma

Abstract: Manganese superoxide dismutase (MnSOD) levels have been found to be low in human pancreatic cancer [Pancreas 26, (2003), 23] and human pancreatic cancer cell lines [Cancer Res. 63, (2003), 1297] when compared to normal human pancreas. We hypothesized that stable overexpression of pancreatic cancer cells with MnSOD cDNA would alter the malignant phenotype. MIA PaCa-2 cells were stably transfected with a pcDNA3 plasmid containing sense human MnSOD cDNA or containing no MnSOD insert by using the lipofectAMINE met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
54
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 17 publications
3
54
0
1
Order By: Relevance
“…While the magnitude and persistence of the effect were similar for both HMEC and SA-NH cells (see Fig. 2, Table 2), the inherent endogenous SOD2 activity measured was greater in non-malignant HMEC, 0.048 ± 0.02 U/10 6 cells, than in mouse tumor SA-NH cells, 0.013 ± 0.002 U/10 6 cells, consistent with reports that cancer cells compared to normal cells are generally low in the enzymatic activities of both SOD1 and SOD2 (30,32,33). SA-NH cells also appeared to require a relatively greater elevation in SOD2 activity than did HMEC to achieve comparable levels of increased radiation protection (see Fig.…”
Section: Discussionsupporting
confidence: 76%
“…While the magnitude and persistence of the effect were similar for both HMEC and SA-NH cells (see Fig. 2, Table 2), the inherent endogenous SOD2 activity measured was greater in non-malignant HMEC, 0.048 ± 0.02 U/10 6 cells, than in mouse tumor SA-NH cells, 0.013 ± 0.002 U/10 6 cells, consistent with reports that cancer cells compared to normal cells are generally low in the enzymatic activities of both SOD1 and SOD2 (30,32,33). SA-NH cells also appeared to require a relatively greater elevation in SOD2 activity than did HMEC to achieve comparable levels of increased radiation protection (see Fig.…”
Section: Discussionsupporting
confidence: 76%
“…Additionally, polymorphisms in this gene have been associated with cancer (60). Some evidence from in vitro studies suggests that superoxide dismutase 2 may act as a tumor suppression gene (61)(62)(63)(64)(65), with increased expression of superoxide dismutase 2 having been shown to suppress the cancer phenotype in a large number of mammalian tumor cells, including human melanoma cells (61,62). We observed down-regulated expression of superoxide dismutase 2 in individuals with skin lesions, which may indicate an increased vulnerability to reactive oxygen species generated by arsenic in individuals with manifest arsenic toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…The significance of the loss of MnSOD expression in cancer cells is underscored by the results of studies that demonstrated MnSOD overexpression can attenuate their malignant phenotypes. [5][6][7] Collectively, these findings have led to the hypothesis that that MnSOD functions as a type of tumor suppressor gene. 8 Breast carcinoma cells and primary tumors generally have lower MnSOD expression and activity than their normal nontumorgenic counterparts.…”
Section: Introductionmentioning
confidence: 99%